KLASIFIKASI JADWAL MENGAJAR DENGAN METODE ANT COLONY OPTIMIZATION - Atmaja, Niko Surya; Lianda, Deri (Jurnal informasi dan komputer, 2023)
Each department in the school has a subject schedule which is arranged in such a way as to ensure the teaching and learning process in that department continues. A good teaching schedule has an even distribution of subjects every day for each level without experiencing obstacles in the teaching and learning process. In preparing the teaching schedule, it is formed based on the number of teachers teaching, number of subjects, number of teaching days and number of classrooms. The problem that occurs is that the large number of classrooms and the small number of teachers makes it complicated to prepare the teaching schedule and you have to re-arrange the teaching schedule, because each time it is prepared there are often conflicts, namely one teacher teaching in a different room at the same time. Therefore, we need a way to make teaching schedules no longer complicated. This research creates an application that can arrange teaching schedules using the Ant colony optimization method so that preparing teaching schedules is no longer complicated.